Development and application of active thermal protection in building facades - Mučková, Veronika; Kalús, Daniel; Muhič, Simon (Vysoké učení technické v Brně,Fakulta stavební, 2025)
This article explores integrating a facade with active thermal protection (ATP) into the Central Laboratories of the Slovak University of Technology in Bratislava. It covers the description of the building as well as ATP installation procedure, and presents preliminary results and recommendations. The study aims to implement ATP, conduct parametric analysis, and perform experimental measurements to assess the ATP performance under various energy functions.
Keywords: Active thermal protection; thermal barrier; heating; cooling